2022
DOI: 10.1111/basr.12267
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 and credit unions: CSR approaches to navigating the pandemic

Abstract: The financial sector plays a fundamental role in Canadian society; credit unions, in particular, cater to a specific group of stakeholders not commonly served by traditional financial institutions. This research investigates the social responsiveness (CSR2) approaches implemented by credit unions during the pandemic, the type of actions implemented, the stakeholders assisted, and whether the size of credit unions may affect their responses. Data were collected from the 100 largest credit unions from nine Canad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 71 publications
(104 reference statements)
0
5
0
Order By: Relevance
“…However, the actions emphasize the agility of credit unions. This means that in a crisis, they were able to respond quickly and imaginatively to the needs of their members by altering their modus operandi (Al‐Zyoud & Ordonez‐Ponce, 2021; Jones et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, the actions emphasize the agility of credit unions. This means that in a crisis, they were able to respond quickly and imaginatively to the needs of their members by altering their modus operandi (Al‐Zyoud & Ordonez‐Ponce, 2021; Jones et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, empirical studies reported that, in response to COVID‐19, cooperatives changed their business activities to service gaps left by other organizational forms (Cooperatives Europe, 2020; Tortia & Troisi, 2021). A small number of empirical studies have examined the responses of credit unions to COVID‐19 in Canada (Al‐Zyoud & Ordonez‐Ponce, 2021), in Britain (Jones et al., 2020), and in Ireland (Money & Mooney, 2020) finding that they altered their modus operandi in timely manner; however, these studies do not examine how credit unions responded as they did. Neither do they provide a comprehensive investigation of the capabilities enabling resilience in cooperatives.…”
Section: Credit Unions and Resiliencementioning
confidence: 99%
See 2 more Smart Citations
“…It's important to consider how to minimize the negative impact of the crisis. Credit Unions have adopted numerous strategies to combat with the economic fallout of the Covid-19 pandemic (Al-Zyoud & Ordonez-Ponce, 2022). Several Credit Unions have implemented accommodating strategies such as debt restructuring, liquidity management, and digitalization (Nguyen et al, 2022).…”
Section: Introductionmentioning
confidence: 99%